European and Anglo Ways of Knowing: Debunking the Coloniality of Power within Local ELT Curriculum - Bonilla Medina, Sandra Ximena; Quintero-Polo, Álvaro Hernán (Colombian Applied Linguistics Journal, 2024)
Editorial